2011
DOI: 10.1007/s00429-011-0306-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of the corticospinal tract in the human brain: a magnetic resonance imaging study at 7 Tesla

Abstract: Several fibre tracts can be accurately located using conventional Magnetic Resonance Images (MRI) of the human brain, including the corticospinal tract (CST), which appears as a T (1)-weighted hypointense/T (2)-weighted hyperintense patch in the posterior part of the posterior-limb of the internal capsule (PLIC). Here we use high-field MRI (7T) to assess the quantitative MRI properties of the CST at the PLIC level in 22 healthy young male participants. We used three different imaging modalities: the T (1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
2
2
0
Order By: Relevance
“…As a result, parallel fibre arrangements, indicated by a low ODI, like in the PLIC, resulted in high FA, based on low radial and high parallel diffusivity as modelled by the diffusion tensor. These results are in line with previous diffusion studies of the CST, which showed high anisotropy at the level of the PLIC and low anisotropy at the level of the centrum semiovale [62,64,65]. On the other hand, in voxels with more complex fibre orientations, like crossings and fanning in the frontal WM and centrum semiovale level of the CST, corresponding FA and eigenvalues are highly influenced by the inhomogeneity of fibre orientations, making them difficult to interpret [44,62].…”
Section: Discussionsupporting
confidence: 93%
“…As a result, parallel fibre arrangements, indicated by a low ODI, like in the PLIC, resulted in high FA, based on low radial and high parallel diffusivity as modelled by the diffusion tensor. These results are in line with previous diffusion studies of the CST, which showed high anisotropy at the level of the PLIC and low anisotropy at the level of the centrum semiovale [62,64,65]. On the other hand, in voxels with more complex fibre orientations, like crossings and fanning in the frontal WM and centrum semiovale level of the CST, corresponding FA and eigenvalues are highly influenced by the inhomogeneity of fibre orientations, making them difficult to interpret [44,62].…”
Section: Discussionsupporting
confidence: 93%
“…Next, we predicted that white matter regions occupied by large-diameter axons would have a lower concentration of myelin (Paus and Toro, 2009). We confirmed this prediction indirectly by observing age-related changes in the “whiteness” of the large-axon cortico-spinal tract (Herve et al, 2009) and, more directly, by showing that this fiber tract, assessed at the level of the internal capsule, has lower MTR values and longer T2 relaxation times than the adjacent (smaller axon) white matter (Herve et al, 2011). We speculated that the presumed testosterone-induced changes in axonal diameter during male adolescence increase the probability of a suboptimal g ratio in the large-diameter fibers and, in turn, decrease conduction velocity in these fibers, as well as perturb axonal transport in these axons (Paus and Toro, 2009).…”
Section: Sex Differences and The Adolescent Brain In Humanssupporting
confidence: 62%
“…Early neuroimaging studies with T1 and T2 MRI sequences evidenced at this exact location an hypersignal corresponding to the highly myelinated PyT fibers (Curnes et al, 1988;Mirowitz et al, 1989;Yagishita et al, 1994). Recent studies have used this hypersignal as a marker to delineate the CST in order to study its asymmetry (Hervé et al, 2009;Hervé et al, 2011). Below the internal capsule, CST and CBT fibers enter the pons by passing through the feet of the cerebral peduncle (Dejerine and Dejerine-Klumpke, 1901).…”
Section: Introductionmentioning
confidence: 99%